1997
DOI: 10.1002/(sici)1097-0134(199707)28:3<388::aid-prot9>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Automated multiple analysis of protein structures: Application to homology modeling of cytochromes P450

Abstract: A computational strategy for homology modeling, using several protein structures comparison, is described. This strategy implies a formalized definition of structural blocks common to several protein structures, a new program to compare these structures simultaneously, and the use of consensus matrices to improve sequence alignment between the structurally known and target proteins. Applying this method to cytochromes P450 led to the definition of 15 substructures common to P450cam, P450BM3, and P450terp, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 67 publications
1
25
0
Order By: Relevance
“…Also, it does not reliably align with the sequences of known structures in areas other than the most conserved regions common to all P450 enzymes. A CYP73A1 homology model was built using the computational strategy, previously described by Jean et al [21] and further improved by Minoletti [22], that identifies substructures, or structurally conserved blocks, in the crystal structures of related proteins, and then locates similar blocks in the target sequence. Common structural blocks of the four P450 structures (P450 BM3 , P450 CAM , P450 TERP , and P450 eryF ) available from the Brookhaven PDB at the start of this work were located in the CYP73A1 sequence as represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, it does not reliably align with the sequences of known structures in areas other than the most conserved regions common to all P450 enzymes. A CYP73A1 homology model was built using the computational strategy, previously described by Jean et al [21] and further improved by Minoletti [22], that identifies substructures, or structurally conserved blocks, in the crystal structures of related proteins, and then locates similar blocks in the target sequence. Common structural blocks of the four P450 structures (P450 BM3 , P450 CAM , P450 TERP , and P450 eryF ) available from the Brookhaven PDB at the start of this work were located in the CYP73A1 sequence as represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The computational homology modelling strategy described by Jean et al [21] allows a reasonable prediction of the most conserved P450 substructures, although hypervariable regions cannot be predicted. Our present model was based on four crystallized bacterial enzymes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After revelation by immunoblotting of these truncated CYP2C9 with a number of anti-LKM2 sera from different patients it became clear that the epitope located in the C-terminal part of the protein was conformational (49). Deletion mutants were tested and those recognized, incorporated in a computer model of CYP2C9 (50), showed that this epitope was located close to the cytosolic surface of the protein. This epitope correspond to a cluster of three helices: helix J (314-322), K (345-356) and L (445-455).…”
Section: Epitope Mapping Of Anti·lkm2mentioning
confidence: 99%